2022
DOI: 10.3390/toxins14070488
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins of Concern in Children and Infant Cereal Food at European Level: Incidence and Bioaccessibility

Abstract: Cereals are of utmost importance for the nutrition of infants and children, as they provide important nutrients for their growth and development and, in addition, they are easily digestible, being the best choice for the transition from breast milk/infant formula to solid foods. It is well known that children are more susceptible than adults to toxic food contaminants, such as mycotoxins, common contaminants in cereals. Many mycotoxins are already regulated and controlled according to strict quality control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…In spite of the regulation framework and continuous monitoring, humans and animals are thus exposed to multiple mycotoxins within a single meal, as biomonitoring studies have demonstrated (Eskola et al, 2020a), (Turner et al, 2012). Current drivers such as new dietary patterns (e.g., increase of alternative protein consumption or plant-based diets) may affect overall exposure, especially in sensitive population groups (Pereira et al, 2022) (i.e., infants, children, pregnant women, people with specific dietary needs).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the regulation framework and continuous monitoring, humans and animals are thus exposed to multiple mycotoxins within a single meal, as biomonitoring studies have demonstrated (Eskola et al, 2020a), (Turner et al, 2012). Current drivers such as new dietary patterns (e.g., increase of alternative protein consumption or plant-based diets) may affect overall exposure, especially in sensitive population groups (Pereira et al, 2022) (i.e., infants, children, pregnant women, people with specific dietary needs).…”
Section: Introductionmentioning
confidence: 99%
“…Several EU regulations currently exist on maximum limits allowed for the most widely recognized mycotoxins, aflatoxin, ochratoxin, zearalenone fumonisin and patulin. These regulations are particularly severe in terms of the limits required for foods and food products destined for infants and children, as they are more susceptible to the effects of mycotoxin contamination [10]. Among the mycotoxins, aflatoxins, produced mainly by Aspergillus flavus, are undoubtedly the most documented of all mycotoxins and are widely present in foods [11].…”
Section: Introductionmentioning
confidence: 99%
“…There are six types of aflatoxins (B 1 , B 2 , G 1 , G 2 , M 1 and M 2 ) [12], where aflatoxin B 1 , AFB 1 , stands out for being considered as Class I carcinogens by the World Health Organization (WHO). More specifically, the bioaccessibility of AFB 1 in infant formulas has been reported to be higher than for other mycotoxins, being, therefore, more toxic [10]. They can be both acutely and chronically toxic and be carcinogenic, mutagenic, teratogenic and immunosuppressive to most mammalian species [13,14].…”
Section: Introductionmentioning
confidence: 99%